Efeitos da adição de óleo essencial de laranja sobre a qualidade do azeite de abacate - Resende, Lívia Maria Braga (2017)
Avocado oil is extracted from avocado pulp. It is similar to olive oil when comparing physicochemical properties and the fruit is cultivated in almost all Brazilian states, and can be extracted in the off-season of olive oil by the same equipments. The consumption of oils like olive and avocado oil is capable of bringing health benefits due to its chemical composition. However, these benefits can be lost during the use and storage of oils, and therefore, alternatives of oils aromatization are being studied in order to improve their sensorial and physicochemical characteristics, since many natural existing flavors can be consumed in food without any detriment to health and have antioxidants characteristics, allowing an increase in shelf life of products. The aim of this work was to evaluate the chemical alterations of avocado oil flavored with different concentrations of orange essential oil, under three different temperatures, performing them to physical-chemical and sensorial tests. The analyzes carried out showed that orange essential oil acts as an antioxidant when added to avocado oil, even with some loss of essential oil after 45 days of storage. The use of avocado oil flavored with orange essential oil under heating was not viable, since the loss of the essential oil was accelerated under these conditions, not showing significant results when compared to unflavored olive oil. Thus, the aromatization of avocado oil with orange essential oil was considered a valid strategy to improve avocado oil conservation.